Does Competition for Clients Increase Service Quality in Cleaning Gobies? - Soares, Marta C.; Cardoso, Sonia C.; Bshary, Redouan; Côté, Isabelle M. (My University, 2008)
In a biological market, members of one trading class try to outbid each other to gain access to the most valuable partners. Competition within class can thus force individuals to trade goods or services more cheaply, ultimately resulting in conflict (e.g. cheating) over the value of commodities. Cleaning symbioses among fish appear to be good examples of biological markets. However, the existence and effect of outbidding competition among either types of traders (cleaners or clients) have never been tested. We examined whether increasing competition among cleaning gobies (Elacatinus spp.) for access to clients results in outbidding in the form of provision of a better cleaning service. On reefs where fish clients visited cleaning stations less frequently, and thus competition among cleaners was higher, cleaning gobies ingested fewer scales relative to the number of ingested parasites, i.e. they cleaned more honestly. This shift in cleaner behaviour towards greater honesty is consistent with a greater market value of access to clients in the face of competition among cleaners. However, this pattern could have also arisen as a result of differences in ectoparasite availability across reefs and therefore in value of the commodity offered by clients. Experimental manipulations will be required to determine whether cleaning service quality by cleaning gobies was enhanced solely because of competitive outbidding.